Maintaining Voting Rights Outside the Election Period: Evidence of Continuous Voter Data Updating (DPB) Riau Province, Indonesia - Yandra, Alexsander; Sudaryanto, Sudaryanto; Asnawi, Eddy; Hernimawati, Hernimawati; Setiawan, Husni; Wijaya, Junior Hendri; Etebom, John Monday (Universitas Muhammadiyah Yogyakarta, 2025)
This study examines the continuous updating of voter data by the General Elections Commission (KPU) based on data self-sufficiency. While previous research has emphasized multi-stakeholder approaches, limited attention has been given to the potential collaboration between the KPU and the Department of Population and Civil Registration (Disdukcapil). Addressing this gap, the study analyzes mechanisms for strengthening inter-agency collaboration to ensure sustainable voter data management. Voting rights are fundamental to political participation and the quality of elections. However, significant gaps persist, as seen in Riau Province where 7,375 citizens were excluded from the voter list before the 2024 Election. This underscores the need for electoral organizers to continuously evaluate and update voter data beyond the election period. Using a qualitative method with an empirical case study approach, the study applies theories of democracy and voters’ political rights, complemented by an ethical–emic analysis. Findings reveal that the KPU remains largely passive in updating sustainable voter data, creating risks of regressive records. Furthermore, coordination with Disdukcapil is one-directional, restricting open access to population data. The novelty of this research lies in highlighting the underexplored institutional collaboration between the KPU and Disdukcapil. Unlike previous studies that focus on broad multi-stakeholder dynamics, this study shows how a targeted inter-agency partnership can directly address voter registration gaps and improve electoral accountability. Strengthening institutional relations through high-level collaboration, routine synchronization, and establishing a dedicated institution for voter data management is therefore essential.